Cultural identity strengthens intercultural attitude in students of an educational institution in Oxapampa, Pasco - Tacuri Toribio, Roberth L. (2024)
The general objective was to demonstrate that cultural identity strengthens the intercultural attitude in the students of the Educational Institution No. 35005 Reverend Father Bardo Bayerle of the Province of Oxapampa 2022. The following methodology was used. Of an applied type, it was proposed to make use of theoretical information of explanatory scope, and an experimental design, with its variant: quasi-experimental with pre-test and post-test in 2 groups, which from now on are called control group and experimental group. . The technique used is the survey since it is a procedure for quantitative research, and the instrument that was used was the questionnaire on the dependent variable. The population is made up of (339) students from the Educational Institution, and the sample consisted of 34 students from the 5th year "A" and 34 from the 5th year "B" making a total of 68 students. The main conclusion was to demonstrate that cultural identity positively strengthens the intercultural attitude, thus demonstrating that there is an improvement in the intercultural attitude of students by promoting dialogue and permanent discussion between different cultural knowledge and practices.